Rede de aprendizagem em robótica : uma perspectiva educativa de trabalho com jovens - Barbosa, Fernando da Costa (2016)
The present research sought to comprehend what is the development perspective of a collective work of educational robotics with high school students. The work started from the development activities Mathematics Sub Project of PIBID (Programa Institucional de Bolsa de Iniciação à Docência, Institutional Program of Initiation to Teaching Scholarship) in a school network from the state of Minas Gerais. The production process of data of this research was done through the follow up of high school students that participated in workshops robotics at the mentioned public school and were selected to continue the project at the Faculty of Mechanical Engineering in Federal University of Uberlândia (UFU). Subsequently, these students were involved in activities related to Robotics championships, elapsed through different spaces in public and private schools of basic education, University and Non-Governmental Organization. The data at the research were registered by photos, videos, field notes, documents produced by the participants and arising from internet like the social media Facebook, questionnaires and, mainly, interviews. At the analysis process of data the followed axes were constituted: Movement Learning Network with Robotics; The Different Roles at the Robotics Events and Experiences in Engineering and Technology. By this axes we understand what is the trajectory of the constitution process of a learning network in educational robotics that we find in expansion and consolidation. In this network the research participants performed different roles which left imprints responsible for their transformation. As a more evident imprint, we detected the robot construction and programming, which as for as they moved their studies forward, they developed the subject autonomy, collaboration, sharing and technological authorship.